Development and validation of bioanalytical method for the determination of valsartan in human plasma - Samir Hasson Aziz Ramadhan (College of Pharmacy / Mustansiriyah University, 2022)
A bioanalytical method which utilizes high performance liquid chromatography with mass spectrometry method has been developed and validated for the quantification of valsartan in human plasma. The samples were processed by precipitation with formic acid then extracted with diethyl ether. Benazepril   was used as an internal standard. The chromatographic separation is performed through C18 column with a mobile phase consisting of deionized water, acetonitrile and formic acid, followed by mass spectrometric detection in the positive ionization mode. The proposed method was specific and had been validated in the linear range of 50.0 - 5000.0 ng/ml for valsartan. The validation results were as follows: the intra-day and inter-day precision were 3.46 to 8.33% and 5.85 to 7.05% respectively, the intra-day and inter-day accuracy were 93.53 to 107.13% and 95.26 to 104.0% respectively. The recovery for valsartan and benazepril was 81.4% and 113.7% respectively. Also, stability was studied and the results obtained for short-term stability 99.24 to 102.32%, for freeze / thaw stability 99.75 to 99.95% and for long-term stability 98.24 to 103.03%. It can be concluded that the method can be applied in pharmacokinetic bioequivalence studies.